2012
DOI: 10.1111/j.1365-2583.2012.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the transcriptional profiles of head and body lice

Abstract: Head and body lice are both blood-feeding parasites of humans although only the body louse is a potent disease vector. In spite of numerous morphological and life history differences, head and body lice have recently been hypothesized to be ecotypes of the same species. We took a comparative genomics approach to measure nucleotide diversity by comparing expressed sequence tag data sets from head and body lice. A total of 10 771 body louse and 10 770 head louse transcripts were predicted from a combined assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…The second study was based on the PM2 spacer [23] and could not show head and body louse divergence within each of the two clusters. Head and body lice were also shown to be genetically indistinguishable in a worldwide study based on four intergenic spacers [24] and in a very recent study based on the louse transcriptome [25]. Finally, based on a Bayesian coalescent model, ancestral migration events between head and body lice were shown to happen in both directions [26].…”
Section: Introductionmentioning
confidence: 81%
“…The second study was based on the PM2 spacer [23] and could not show head and body louse divergence within each of the two clusters. Head and body lice were also shown to be genetically indistinguishable in a worldwide study based on four intergenic spacers [24] and in a very recent study based on the louse transcriptome [25]. Finally, based on a Bayesian coalescent model, ancestral migration events between head and body lice were shown to happen in both directions [26].…”
Section: Introductionmentioning
confidence: 81%
“…A recent review includes the information on the specific sequences found in parasites and their homologies with miRNA sequences of other organisms [2]. After this review, the number of identified miRNA sequences in parasites in which miRNAs were already known has increased due to large scale sequencing experiments, and new miRNA sequences have been also described in parasites in which miRNAs had not been evidenced before (see http://www.mirbase.org/search.shtml; [12][13][14][15]; Fig. 1).…”
Section: Micrornas In Parasites: a Growing Collection Of Sequence Infmentioning
confidence: 99%
“…Similarly, human body lice are thought to have emerged as an alternative morph of human head lice since the use of clothing became widespread. While there were no significant differences detected in which genes were expressed between the two morphs [34], morph-specific alternative splicing events were detected for over a thousand genes [35]. In particular, body lice-specific alternative splicing events were enriched in genes associated with developmental gene ontology terms [35].…”
Section: Introductionmentioning
confidence: 96%